Socialization of The Role of Entrrepreneurial Orientation in Exsploiting Business Opportunities for Tempe Entrepreneurs - Nawangsih Nawangsih (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The problems faced by business actors include: entrepreneurial orientation of business actors who are still limited, the ability to innovate by creating new businesses by utilizing tempe is also still limited, so socialization is needed to provide an overview of knowledge in business development. These businesses are carried out from generation to generation, some even use simple equipment so that the resulting productivity is not maximized and the ability and courage of business actors to diversify and differentiate the products produced is also still limited, so the products produced are still limited. tempe variant a little. Based on these conditions, socialization activities related to the role of entrepreneurship orientation in taking advantage of business opportunities for entrepreneurs can be the best solution to help provide solutions to problems that lie above these business actors, because entrepreneurship is right in taking advantage of business opportunities. This opportunity can be an opportunity to create new business opportunities that are more diverse and useful to improve the welfare of tempe entrepreneurs, as well as produce more diverse tempe products so that they can provide a more diverse choice of preferences for consumers and provide added value and separate appeal. of the resulting product.